Genome-wide identification and expression analysis of the CONSTANS-like family in potato (Solanum tuberosum L.) - Yin, Wang; Wang, Luo; Shu, Qiqiong; Chen, Mingjun; Li, Fei; Luo, Xiaobo (Frontiers in Genetics, 2024)
gene plays important roles in plant growth, development and abiotic stress. A total of 15 COL genes are unevenly distributed on 8 chromosomes in the potato genome. The amino acid length of the family members was 347-453 aa, the molecular weight was 38.65-49.92 kD, and the isoelectric point was 5.13-6.09. The StCOL family can be divided into three subfamilies by evolutionary tree analysis, and with conserved motifs and similar gene structure positions found within each in the same subfamily. The analysis of promoter cis-acting elements showed that a total of 17 cis-acting elements related to plant hormones, stress and light response.Collinearity analysis of COL genes of tomato, potato and Arabidopsis showed that 13 StCOL genes may have a common ancestor in different species and evolved from the same ancestor. A total of 10 conserved motifs and 6 kinds of post-translational modifications in the 15 StCOL proteins were identified. The 15 StCOL genes exhibit a genomic structure consisting of exons and introns, typically ranging from 2 to 4 in number. The results showed that 13 genes displayed significant expression across all potato tissues, while the remaining 5 genes were down-expressed in potato transcriptome data. The qRT-PCR analysis exhibited differential expression of10 StCOL genes in the potato leaves and tube at different growth stages, as well as 9 StCOL genes under 2 °C treatment conditions. These results suggested that the StCOL gene family may play an important role in regulating potato tuberization and responding to cold stress.